Penerapan Konsep Healing Environment pada Strategi Perancangan Pusat Pelayanan Lanjut Usia di Surakarta - Mintari Nur Aziza; Hari Yuliarso; Hardiyati Hardiyati (Universitas Sebelas Maret Surakarta, 2019)
When entering the elderly phase, humans will experience a physical and psychological conditions declined, this causes the elderly to need special and different services compared to normal adults. In order to overcome these problems, also to reach Surakarta as an Elderly Friendly City, a Elderly Care Center is needed as a place that provides various services needed by the elderly. This care center requires a healing environment concept that can create a conducive environment so that it can restore and improve physical and psychological health conditions of the elderly. In order to achieve healing environment, there are some approaches that can be done, such as the sensory approach (sense of sight, sense of touch, sense of hear, and sense of smell), natural approach (healing garden), and psychological approach. The method that used are observational studies to the community, field studies, and literature studies on related theories. The approaches og healing environment concept can be applied in the analysis of planning and design, so that will result the Eldelry Care Center with an environment where the elderly can easily adapt, feel comfortable, safe, and can support the recovery and improvement of the physical and psychological conditions of the elderly.